Haloxylon ammodendron adapts to desert environments through seed polymorphism during diaspore germination and seedling establishment - Wang, Ziyi; Chen, Weizhi; Yang, Minghao; Jiang, Lamei; Wang, Ze; Ren, Cai; Zhang, Xianhua (Frontiers in Plant Science, 2025)
IntroductionSeed polymorphism, defined as the production of two or more types of diaspores with distinct morphology and ecological function within a species, represents a bet-hedging strategy that enables plants to cope with unpredictable spatiotemporal environmental variability. Previous studies have mainly focused on annual plants; therefore, little is known about in perennial species, particularly in desert constructive plants.MethodsThis study investigated seed polymorphism in Haloxylon ammodendron, a foundational desert shrub critical for maintaining the stability of fragile arid ecosystems. Field surveys, morphological characterization, phytohormone quantification, germination assays, and seedling growth analyses were conducted to elucidate the ecological significance of seed polymorphism in this species.Results and discussionSeed polymorphism was prevalent across natural populations within the study region, with different plants producing three distinctly colored diaspores: YY (yellow fruit-wing perianth and yellow pericarp), YP (yellow fruit-wing perianth and pink pericarp), and PP (pink fruit-wing perianth and pink pericarp). The fruit/diaspore biomass and gibberellic acid/abscisic acid ratio were the lowest in YY (0.611 and 0.64, respectively) and the highest in YP (0.684 and 1.56). YY plants exhibited grater drought resistant and produced fewer but more robust seedlings, ensuring population persistence. YP seeds have a higher germination percentage, germination rate, and emergence percentage, facilitating rapid population expansion under favorable conditions. PP seeds showed reduced germination under salt stress, suggesting a potential role as a persistent soil seed bank. These results indicate that H. ammodendron employs seed polymorphism to adapt to unpredictable desert environment during diaspore germination and seedling establishment. This study enhances the theoretical understanding of the bionomic strategies underpinning plant adaptation to extreme environments, with implications for population persistence and regeneration dynamics, while also providing diversified germplasm resources for desertification prevention.